Meningkatkan Prestasi Akademik Siswa Kelas III Mata Pelajaran Pkn Materi Pokok Mencerminkan Harga Diri Menggunakan Metode Diskusi - Devi Fadilah; Dina Syaflita (Kilau Publishing, 2023)
The primary objective of this study is to elevate the academic performance of third-grade students at Tanjungmekar I Elementary School in the domain of Citizenship Education (PKN) through the utilization of the discussion method, which specifically focuses on nurturing self- esteem. Utilizing a qualitative approach with a classroom action research design, this investigation involved the active participation of 23 students. The data collection process encompassed thorough classroom observations, interviews conducted with both the teacher and students, and comprehensive learning achievement tests. By implementing the discussion method as an instructional strategy, the researchers aimed to stimulate students' active involvement in the learning process of PKN. The results revealed a noteworthy enhancement subsequent to the implementation of the discussion method. Initially, during the pre-test phase, students achieved an average score of 64.5. However, following three cycles of employing the discussion method, the average score escalated to 82.5. Thus, it can be inferred that the discussion method effectively augments students' learning outcomes in the PKN subject within the third grade of Tanjungmekar I Elementary School.